2020
DOI: 10.1371/journal.pntd.0008735
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of food sources, ecotypic distribution and Trypanosoma cruzi infection in Triatoma brasiliensis from the northeast of Brazil

Abstract: Innovative approaches used to combat Chagas disease transmission tend to combine a set of comprehensive efforts to understand the ecology of local vectors. In this work we identified molecularly the blood meal of 181 Triatoma brasiliensis, distributed in 18 populations (8 sylvatic and 10 peridomestic), which were collected across a range of 240 km (East-West) and 95 km (North-South) in the semi-arid region of northeastern, Brazil. We used the vertebrate mitochondrial gene (cytochrome B) sequencing applied to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…The triatomines of the T. sherlocki species analysed fed on mammals, birds and reptiles, totaling nine different vertebrate species, highlighting the feeding eclecticism of this triatomine. This dietary diversity, as well as that found in the species T. brasiliensis , which is considered as domiciled in northeastern Brazil (Lilioso et al, 2020; Lima‐Neiva et al, 2021), may lead to a future domiciliation of T. sherlocki , since these two species belong to the same complex. Other studies point to a wide diversity of food sources of domestic and wild triatomines, such as the species of: (i) triatomine Rhodnius ecuadoriensis , which in Ecuador is considered as domiciled, but is often captured in the wild.…”
Section: Discussionmentioning
confidence: 62%
“…The triatomines of the T. sherlocki species analysed fed on mammals, birds and reptiles, totaling nine different vertebrate species, highlighting the feeding eclecticism of this triatomine. This dietary diversity, as well as that found in the species T. brasiliensis , which is considered as domiciled in northeastern Brazil (Lilioso et al, 2020; Lima‐Neiva et al, 2021), may lead to a future domiciliation of T. sherlocki , since these two species belong to the same complex. Other studies point to a wide diversity of food sources of domestic and wild triatomines, such as the species of: (i) triatomine Rhodnius ecuadoriensis , which in Ecuador is considered as domiciled, but is often captured in the wild.…”
Section: Discussionmentioning
confidence: 62%
“…Recently, was observed that reptile blood is the main food source for T. petrocchiae [78]. On the other hand, T. b. brasiliensis is mainly associated with rodents [49]. Taking into account that these two taxa live in sympathy [50], it is likely that the ecological (or habitat) isolation is the main pre-zygotic barrier that makes unfeasible the formation of natural hybrids between T. petrocchiae and T. b. brasiliensis.…”
Section: Plos Onementioning
confidence: 99%
“…Other transmission routes, such as oral and congenital routes, are also important in some endemic countries [ 1 , 5 ]. It is important to highlight that oral transmission is also vector dependent as infected insects are responsible for food or drink contamination [ 6 ].…”
Section: Introductionmentioning
confidence: 99%